Potential no man's land for the 4th year dental graduate. Issue 1 (January 2022) - Bradshaw, T.; Godden, D.R.P.; Coyle, M.J.; Finley, B.; Beaumont, I.; Beech, A.N.
Abstract: The Royal College of Surgeons of England stipulates that to hold a substantive specialty or associate specialist (SAS) grade post a person must be a minimum of 4 years post-graduation and have at least 2 years' experience in their chosen speciality. We have noticed an increasing number of excellent applications for specialty doctor adverts posted by our trust without the necessary 4 years of post-graduate experience. Many of these applicants who do not comply with the RCS stipulations may be forced to take a job outside of their chosen career path. The reasons for this may be multifactorial, but it could have a worrying impact on their own future career and hospital service provision. We looked at the number of SAS grade adverts placed on NHS jobs in the year 2019 and the type of job advertised. We also considered the possible reasons for a rise in the number of applicants for SAS roles in oral surgery and oral and maxillofacial surgery, and what changes, if any, could be made to support this group of clinicians.